Islamic Community Empowerment in Economic Growth through Sugar Cane Farming Partnerships - Rini Setiawati; Heni Noviarita; Sri Haryanto; Mubasit Mubasit; Daryono Daryono; Afif Anshori; Agus Dwianto (Qubahan Academic Journal)
This is an exploratory research investigating the links for dependency, sugarcane harvesting and even (handful of) Islamic communities which establish these connections. It uses a mixed method that combines quantitative and qualitative elements along with an exploratory case study to explore the coordination mechanisms between global agribusiness giants' strategies and local sugarcane suppliers. This is the kind of integration needed to promote an ethical economy, where all parties involved are moving in the same direction towards a common appreciation for human success and well-being. Existing structure, however is embroiled in transaction costs of top-heavy governance contracts and inadequate farmer engagement with a complete contradiction to the basic principles of Islamic economic behaviour. Results from focus groups suggest the necessity of more farmer inclusion, hands-on exposure to field work and further intergroup collaboration. These components plus the principles of solidarity and “no worker left behind” with rigorous training requirements, monitoring can increase benefits to workers. This information provides a vital resource for practitioners, educators and policy makers to implement Islamic law in agriculture taking into consideration an organized rural development.